Political Connections, Fees Paid to Auditors and Auditor Independence in Malaysia: Evidence From Going Concern Audit Opinions - Abdul Wahab, Effiezal Aswadi; Zain, M.; Rahman, R. (Inderscience Publishers, 2013)
This study examines whether auditor independence will be affectedby the magnitude of audit and non-audit services fees provided to audit clientsand political connections. We predict that auditor independence will beundermined when audit firms provide non-audit services to the audit clients asthe provision of the non-audit services to audit clients increases the economicbond between the audit firm and the client. Furthermore, given the uniqueinstitutional background in Malaysia, we also test the relationship betweenauditor independence and political connections. We use the propensity to issuea going concern opinion as a proxy for auditor independence while politicalconnections are represented by two measures namely the proportion ofBumiputras directors on the board and politically connected firms. Contrary toour prediction, we do not observe any association between the propensity toissue going concern opinions and non-audit fees, total fees and the ratio ofnon-audit fees to total fees. Interestingly, we find evidence to suggest thataudit firms are less likely to issue going concern opinions when audit clientshave more Bumiputras directors sitting on board. This result is view to beimportant as it suggests that political connections could undermine auditorindependence in fact and appearance.